Low current performance of the Bern medical cyclotron down to the pA range. (30th July 2015) - Auger, M; Braccini, S; Ereditato, A; Nesteruk, K P; Scampoli, P
Abstract: A medical cyclotron accelerating H − ions to 18 MeV is in operation at the Bern University Hospital (Inselspital). It is the commercial IBA 18/18 cyclotron equipped with a specifically conceived 6 m long external beam line ending in a separate bunker. This feature is unique for a hospital-based facility and makes it possible to conduct routine radioisotope production for PET diagnostics in parallel with multidisciplinary research activities, among which are novel particle detectors, radiation biophysics, radioprotection, radiochemistry and radiopharmacy developments. Several of these activities, such as radiobiology experiments for example, require low current beams down to the pA range, while medical cyclotrons are designed for high current operation above 10 μ A. In this paper, we present the first results on the low current performance of a PET medical cyclotron obtained by ion source, radio-frequency and main coil tuning. With this method, stable beam currents down to ( ) pA were obtained and measured with a high-sensitivity Faraday cup located at the end of the beam transport line.